THE EFFECT OF RELIGIOUS LEVEL AND PERCEPTIONS OF RIBA ON INTEREST IN SAVING IN SHARIA BANKS: Study on MSME Businessmen in Kasihan District, Bantul Regency - Abdul Rahim; Dunyati Ilmiah (NUsantara Islamic Economic Journal, 2022)
Islamic Bank is a Bank which in carrying out its activities based on Islamic principles. The purpose of this study was to determine the effect of the level of religiosity and perceptions of usury on the interest of MSME businessman in Kasihan District, Bantul to save at Islamic banks. This type of research is quantitative research with a sample of 42 MSME actors. The data collection technique in this study used a questionnaire. The data analysis technique used is descriptive analysis, classical assumption test and multiple linear regression analysis. From the results of the analysis, it can be concluded that the level of religiosity does not have a positive and significant effect on the interest in saving for MSME actors in Kasihan District, Bantul in Islamic Banks. Perceptions of usury have a positive and significant influence on the interest in saving for MSME actors in Kasihan District, Bantul in Islamic Banks. The level of religiosity and perceptions of usury together have an influence on the saving interest of MSME actors in Kasihan District, Bantul in Islamic Banks.